THE INDONESIAN JOURNALISTS ASSOCIATION (PWI) IN RIAU DURING THE NEW ORDER ERA 1968-1998: Persatuan Wartawan Indonesia (PWI) Riau Pada Masa Orde Baru Tahun 1968-1998 - Dhanti Salsabila Azis; Bunari; Ahmal (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The Minister of Information Regulation in Indonesia in 1969 stipulated that Indonesian journalists are required to become members of an Indonesian journalists’ organization approved by the government. Until June 1998, only one organization, the Indonesian Journalist Association (PWI), was recognized. In Riau, PWI was first chaired by H. Moeslim Roesli, serving from 1966-1968. Previously, in August 1963, a temporary representation of PWI Riau was formed with the following structure: Aspan Diar – Chairperson, A. Moeis Hadjads – Vice Chairperson, Noerbahrij Joesoef – Secretary, G.N.T Ilyas – Vice Secretary, Harun Al Rasyid – Treasure, accompanied by two Commissioners, A. Rachman Junus XI. The method used in this research is the Historical method. The historical method seeks to study past events, describing and analyzing these facts in depth. PWI Riau has several roles for journalists aimed at achieving common goals. And PWI Riau faces several challenges that they can resolve professionally through their activities.